2022
DOI: 10.7759/cureus.30226
|View full text |Cite
|
Sign up to set email alerts
|

The Holistic Review on Occurrence, Biology, Diagnosis, and Treatment of Oral Squamous Cell Carcinoma

Abstract: A prevalent head and neck cancer type is oral squamous cell carcinoma (OSCC). It is widespread and associated with a high death rate of around 50% in some regions of the world. We discuss the likelihood of developing OSCC and the impact of age in this review. Prior to examining the vast array of diagnostic indicators, a brief explanation of the biology of the disease is addressed. Finally, the therapeutic strategies for OSCC are listed. The complete literature for this study was compiled by searching Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…From the data of recent researchers, it can be hypothesised that the process of malignant transformation and its further progression is facilitated through interactions among epithelial and connective tissue components, chiefly collagen and elastic fibres. [ 13 , 14 ] Data from different animal research models also provide substantial evidence that fibrotic disorders have the malignant potential and there exist oncogenic factors in both the afflicted tissues. Referring to this with OSMF, it can be suggested that epithelial-mesenchymal interactions might result in significant alterations of epithelial phenotype, thereby increasing the possibilities of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…From the data of recent researchers, it can be hypothesised that the process of malignant transformation and its further progression is facilitated through interactions among epithelial and connective tissue components, chiefly collagen and elastic fibres. [ 13 , 14 ] Data from different animal research models also provide substantial evidence that fibrotic disorders have the malignant potential and there exist oncogenic factors in both the afflicted tissues. Referring to this with OSMF, it can be suggested that epithelial-mesenchymal interactions might result in significant alterations of epithelial phenotype, thereby increasing the possibilities of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Oral carcinoma is the most frequent cancer in the head and neck area [ 1 ]. Oral squamous cell carcinoma (OSCC) represents 90000 of all types of oral cancers [ 2 ], ranking sixth among all forms of carcinomas worldwide [ 3 ]. Tobacco and alcohol consumption, as well as human papillomavirus (HPV), are the most common independent risk factors for OSCC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral cancer is a common oral and maxillofacial cancer that accounts for approximately 3% of all malignant tumors [1]. Although the incidence is lower than that of other malignant tumors, it is often accompanied by local invasion and distant metastasis during diagnosis and treatment, and the overall 5-year survival rate is only 50-55% [2]. The cure rate of patients with focal or regional invasion is < 30%, which is poor given the improvements in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The cure rate of patients with focal or regional invasion is < 30%, which is poor given the improvements in cancer treatment. The survival rate is difficult to improve, mainly because oral cancer is often not diagnosed at an early stage [2][3][4].…”
Section: Introductionmentioning
confidence: 99%